Assembly of a Nanoreactor System with Confined Magnetite Core and Shell for Enhanced Fenton‐Like Catalysis. Issue 21 (15th April 2014) - Zeng, Tao; Zhang, Xiaole; Wang, Saihua; Ma, Yurong; Niu, Hongyun; Cai, Yaqi
Abstract: Conventional solid catalysts for heterogeneous Fenton‐like reactions in bulk solution usually suffer from aggregation and vulnerability, which greatly lower the catalytic efficiency and hamper their practical application. Herein, we demonstrate a promising yolk–shell nanostructure with both the core and the shell composed of magnetite (designated as yolk‐like Fe3 O4 @Fe3 O4 /C) as a nanoreactor capable of accommodating the Fenton‐like reaction into its void space. Benefiting from the mesoporous shell and perfect interior cavity of this composite, reactants can access and be abundantly confined within the microenvironment where Fe3 O4 sites are dispersed on the entire cavity surfaces, thus leading to a higher catalytic efficiency compared with the conventional solid catalysts in bulk solution. The chosen model reaction of chlorophenols degradation in the presence of the as‐prepared materials as well as hydrogen peroxide (H2 O2 ) confirms this assumption. Under the optimal reaction conditions, more than 97 % 4‐chlorophenol (4‐CP) can be degraded in the Fe3 O4 @Fe3 O4 /C nanoreactor, whereas only 28 % can be achieved by using bare Fe3 O4 particles within 60 min. Furthermore, owing to the existence of the outermost carbon layer and high‐magnetization properties, the nanoreactor can be re‐used for several runs. The synthesized nanoreactor displays superior catalytic activity toward the Fenton‐like reaction compared with the bare solid catalysts, and thereby holds significant potential for practical application in environmental remediation. Abstract : An unconventional shell : A novel yolk–shell nanostructure in which both the core and the shell are composed of magnetite (designated as yolk‐like Fe3 O4 @Fe3 O4 /C) functions as a nanoreactor for the Fenton‐like reaction, displaying enhanced catalytic activity compared with conventional solid catalysts (see figure).